The Safety Paradox of Digitalized Wilderness Among Novice Travelers in Indonesian National Parks - Eko Susanto; Mega Fitriani Adiwarna Prawira (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2026)
This study aims to explicitly investigate the complex interplay between User-Generated Content (UGC) exposure, Travel FOMO, risk mitigation, and post-trip behavioral outcomes among novice national park visitors. Employing a cross-sectional quantitative design and purposive sampling, this research analyzed 601 novice travelers (Generation Z and Millennials) visiting Indonesian national parks. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results indicate that UGC triggers both FOMO and Risk Mitigation Behavior (RMB). However, FOMO fails to drive rational preparedness. A Safety Paradox is confirmed: mitigation efforts intensify perceived trail difficulty, which paradoxically enhances mindfulness and Nature Connectedness. This process ultimately drives Experiential Satisfaction, Environmental Stewardship, and e-WOM advocacy. This study extends Protection Motivation Theory by identifying a digital affective bias in which social anxiety overrides objective safety. It further enriches the Adventure Experience Paradigm by proving that logistical preparedness effectively shatters the illusion of ease perpetuated by social media.